PENDIDIKAN ISLAM DAN ENTERPRENEURSHIP - Aziz Azis (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Abstract: Islamic education is closely related to entrepreneurship, which guides and supports success. also gave the spirit of reaching a goals, can treat liver fall in failure. In the world of education, entrepreneurship spirit becomes a critical success pupils and students, from primary schools, secondary to college. As for the subject of entrepreneurship is an attitude of independence. While the definition of independence is an attitude and behavior that is not easily dependent on others to complete tasks. Independence of a person would be better, if supported by positive qualities, such as, confident, honest, hard work, discipline, dare to take risks, motivation, optimism, teamwork, innovative and so forth. Keywords; Islamic Education, Independence, Entrepreneurship